A 3D free-standing lithiophilic silver nanowire aerogel for lithium metal batteries without lithium dendrites and volume expansion: in operando X-ray diffraction. Issue 40 (23rd April 2019) - Phattharasupakun, Nutthaphon; Wutthiprom, Juthaporn; Duangdangchote, Salatan; Sawangphruk, Montree
Abstract : A 3D free-standing lithiophilic silver nanowire aerogel (AgNWA) can stop the dendritic growth of lithium metal at the initial nucleation process. Abstract : A 3D free-standing lithiophilic silver nanowire aerogel (AgNWA) can stop the dendritic growth of lithium metal at the initial nucleation process. The 3D structure can also suppress the infinite volume expansion of lithium during cycling. The active AgNWA scaffold can serve as a Li reservoir to compensate for the irreversible consumption of Li. The lithiated AgNWA anode was coupled with a lithium iron phosphate (LFP) cathode in a full-cell configuration providing much higher performance than the Li//LFP cell.